Pengaruh Kepuasan Wisatawan Dan Citra Destinasi Terhadap Minat Kunjungan Ulang Di Kota Lama Semarang - Aletta Dewi Maria; Ray Octafian; Dyah Palupiningtyas; Isnu Hadi Sunarko; Muhammad Arif Winata; Perez Eben Ezer Sidabutar (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
The Old Town of Semarang is a famous tourist destination in Indonesia, with the potential to captivate tourists to return. This study aims to examine the impact of tourist satisfaction and perception of destination image on the intention to revisit the Old Town of Semarang. The research employs a quantitative approach through a survey. Data was collected through questionnaires given to tourists visiting the Old Town of Semarang. The research findings indicate that tourist satisfaction and destination image have a positive and significant influence on the intention to revisit. Tourist satisfaction positively contributes to the intention to revisit because satisfied tourists are more likely to return. Additionally, destination image also positively influences the intention to revisit as tourists with a positive perception of the destination are more likely to return. These findings provide insights for tourism destination managers to enhance tourists' interest in revisiting.